Mucoadhesive Nanocarriers as a Promising Strategy to Enhance Intracellular Delivery against Oral Cavity Carcinoma - Manisha Pandey; Hira Choudhury; Jenifer Ngu Shao Ying; Jessica Foo Sze Ling; Jong Ting; Jocelyn Su Szhiou Ting; Ivory Kuek Zhia Hwen; Ho Wan Suen; Hazimah Syazwani Samsul Kamar; Bapi Gorain; Neha Jain; Mohd Cairul Iqbal Mohd Amin (MDPI AG, 2022)
Oral cancer, particularly squamous cell carcinoma (SCC), has posed a grave challenge to global health due to its high incidence, metastasis, and mortality rates. Despite numerous studies and favorable improvements in the therapeutic strategies over the past few decades, the prognosis of this disease remains dismal. Moreover, several drawbacks are associated with the conventional treatment; including permanent disfigurement and physical impairment that are attributed to surgical intervention, and systemic toxicity that results from aggressive radio- or chemotherapies, which impacts patients' prognosis and post-treatment quality of life. The highly vascularized, non-keratinized oral mucosa appears as a potential route for cytotoxic drug administration in treating oral cancer. It acts as a non-invasive portal for drug entry targeting the local oral lesions of the early stages of cancer and the systemic metastasis sites of advanced cancer. The absorption of the poorly aqueous-soluble anti-cancer drugs can be enhanced due to the increased permeability of the ulcerous mucosa lining in the disease state and by bypassing the hepatic first-pass metabolism. However, some challenges in oral transmucosal drug delivery include the drugs' taste, the limited surface area of the membrane lining the oral cavity, and flushing and enzymatic degradation by saliva. Therefore, mucoadhesive nanocarriers have emerged as promising platforms for controlled, targeted drug delivery in the oral cavity. The surface functionalization of nanocarriers with various moieties allows for drug targeting, bioavailability enhancement, and biodistribution at the site of action, while the mucoadhesive feature prolongs the drug's residence time for preferential accumulation to optimize the therapeutic effect and reduce systemic toxicity. This review has been focused to highlight the potential of various nanocarriers (e.g., nanoparticles, nanoemulsions, nanocapsules, and liposomes) in conferring targeting, solubility and bioavailability enhancement of actives and mucoadhesive properties as novel tumor-targeted drug delivery approaches in oral cancer treatment.